(untitled) (Journal of Bio-Science, 2026)
This study examined the effects of metformin and glimepiride on glycated hemoglobin (HbA1c) and lipid profiles in patients with type 2 diabetes mellitus (T2DM). The study was conducted over six months in an outpatient diabetes clinic. It includes adults aged 18-70 with HbA1c levels between 7% and 10%. Participants were treated with metformin (500-1000 mg) or glimepiride (1-4 mg), with dose adjustments based on glycemic control. HbA1c, fasting blood glucose, and lipid profiles were assessed at baseline and after six months. The results showed significant improvements in HbA1c, lipid profiles, mental health, and patient satisfaction. HbA1c levels decreased from 7.02% to 6.23% (p<0.001), and lipid profiles improved, with triglycerides dropping from 245 mg/dl to 180 mg/dl, total cholesterol from 271 mg/dl to 225 mg/dl, LDL from 165 mg/dl to 151 mg/dl, and HDL increasing from 35 mg/dl to 42 mg/dl (p<0.001). Depression and anxiety scores also improved significantly, along with higher patient satisfaction. The study concluded that metformin and glimepiride effectively improved glycemic control, lipid metabolism, and mental health in T2DM patients, highlighting their broader benefits beyond glucose regulation. These findings support their role in comprehensive diabetes management. J. Bio-Sci. 33(1): 01-11, 2025